Low Rise Apartment Design - Irfan Aldyanto; Husna Izzati; Andiyan Andiyan (Jurnal Arsitektur Archicentre, 2022)
Kota Baru Parahyangan is a rapidly growing independent city with many facilities including Residential, Commercial, Recreational, and Public Areas. In addition, Kota Baru Parahyangan has an integrated and directed area development plan called the Town Center, which will be developed into a "City Center". And to support the efforts of the Master Plan Town Center development plan, a vertical Low Rise Apartment with the concept of a High-end Apartment is designed; with the existence of vertical Low Rise Apartment housing in Kota Baru Parahyangan, it is hoped that it will provide more diverse residential options. excluding Landed House and Landed House. In addition, applying Tropical Contemporary Architecture is anticipated to produce a building with a modern façade that responds well to the weather and surrounding environment, resulting in an aesthetically and thermally rhythmic structure. This design is based on field observations, comparative studies, and literary research connected to the building, followed by site analysis and application of architectural principles, which are then depicted in the form of two-dimensional (2D) and three-dimensional (3D) working drawings) (3D).